A review of Quizizz – a gamified student response system (Journal of Applied Learning and Teaching, 2022)
The purpose of this EdTech review is to highlight the main features of Quizziz as an online tool for formative assessment. It can be used during online or face-to-face delivery and both synchronously and asynchronously. Quizizz is a gamified student response system that has been available since 2015. It was created by a homonymous startup based in Bengaluru (India). By end-2020, Quizizz had more than 65 million monthly active users in more than 150 countries (Naik, 2020).